Efficacy and Safety of Emricasan in Liver Cirrhosis and/or Fibrosis (Clinics, 2021)
This study aimed to perform a meta-analysis to determine the efficacy and safety of emricasan.Nine databases were searched for clinical trials investigating the efficacy of emricasan treatment in patients with liver cirrhosis or fibrosis. A manual search was conducted to identify the missing trials. The quality of the included studies was assessed using the revised Cochrane risk of bias tool. Efficacy of emricasan treatment was defined as a positive change in apoptosis-related parameters from baseline to the last follow-up visit.Overall, emricasan treatment is more effective in patients with liver cirrhosis or fibrosis than placebo (standardized mean difference [SMD] [95% confidence intervals (CI)]=0.28 [0.14; 0.41]). No significant change in model for end-stage liver disease (MELD) score between the emricasan and placebo groups was noted (SMD [95% CI]=0.18 [-0.01; 0.36]; p=0.058). A 50 mg dose of emricasan had the highest efficacy rate compared to placebo (SMD [95% CI]=0.28 [0.06; 0.50]; p=0.012), followed by the 5 mg dosing regimen (SMD [95% CI]=0.28 [0.06; 0.50]; p=0.012). Treatment with emricasan resulted in significant reductions in ALT (mean difference (MD) [95% CI]=-5.89 [-10.59; -1.20]; p=0.014) and caspase3/7 levels (MD [95%CI]=-1215.93 [-1238.53; -1193.33]; p<0.001), respectively. No significant increase in the rate of overall adverse events was noted (OR [95% CI]=1.52 [0.97; 2.37]; p=0.069).Treatment with emricasan is more effective in improving liver function and apoptosis parameters compared to placebo, with a well-tolerated safety profile. However, due to the poor quality of the analyzed studies, the small number of trials and patients, and the short follow-up periods, more robust trials are still warranted.